Foreign equity flows: Boon or bane to the liquidity of Malaysian stock market? - Liew, Ping Xin; Lim, Kian Ping; Goh, Kim Leng (Elsevier, 2018)
This paper examines the impact of gross foreign equity inflows on aggregate liquidity of the Malaysian stock market using newly assembled foreign trading data and the best performing bid-ask spread proxy. Employing vector autoregression, we discover a one-way causality from gross inflows to aggregate liquidity, and foreign investors erode liquidity of the Malaysian stock market. Additional analyses reveal that uncertainties in the U.S. markets negatively affect aggregate liquidity through the flows of foreign institutions, whose positive feedback trading destabilizes the local bourse. Despite the shocks, there is sufficient liquidity provision from local state-backed institutional funds and local proprietary day traders.